2010
DOI: 10.1016/j.supflu.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of phenol with supported Rh catalysts in the presence of compressed CO2: Its effects on reaction rate, product selectivity and catalyst life

Abstract: Hydrogenation of phenol to cyclohexanone and cyclohexanol in/under compressed CO 2 was examined using commercial Rh/C and Rh/Al 2 O 3 catalysts to investigate the effects of CO 2 pressurization on the total conversion and the product selectivity. Although the total rate of phenol hydrogenation with Rh/C was lowered by the presence of CO 2 , the selectivity to cyclohexanone was improved at high conversion levels > 70%. On the other hand, the activity of Rh/Al 2 O 3 was completely lost in an early stage of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 57 publications
5
30
0
1
Order By: Relevance
“…Cyclohexanone and cyclohexanol result from hydrogenation of phenol while cyclohexanol is also produced from cyclohexanone hydrogenation. This reaction scheme is in good agreement with that proposed by Fujita et al [47] for the hydrogenation of phenol using supported Rh catalysts. Other useful reaction scheme has been proposed by Diaz et al [11] for the HDC of 4-CP using alumina-supported Pd, Pt and Rh catalysts.…”
Section: Selectivity Of Rh Nanoparticlessupporting
confidence: 92%
See 1 more Smart Citation
“…Cyclohexanone and cyclohexanol result from hydrogenation of phenol while cyclohexanol is also produced from cyclohexanone hydrogenation. This reaction scheme is in good agreement with that proposed by Fujita et al [47] for the hydrogenation of phenol using supported Rh catalysts. Other useful reaction scheme has been proposed by Diaz et al [11] for the HDC of 4-CP using alumina-supported Pd, Pt and Rh catalysts.…”
Section: Selectivity Of Rh Nanoparticlessupporting
confidence: 92%
“…8, the following kinetic model is proposed for the HDC process to gain insight into the issue. This model is similar to that proposed by Fujita et al [47] for the hydrogenation of phenol using Rh-based catalysts, but including the step of HDC of 4-CP to phenol.…”
Section: Kinetic Analysissupporting
confidence: 61%
“…For example, in hydrogenation of phenol with Rh catalysts supported on C and Al 2 O 3 , the Rh/C does not lose its activity during the reaction but the Rh/Al 2 O 3 is easily deactivated at an early stage of reaction [17]. This difference is caused by weak and strong adsorption of CO (originating from CO 2 ) on the former and latter catalysts, respectively, as proved by in situ FTIR measurements.…”
Section: Introductionmentioning
confidence: 91%
“…In the present work, the features of such a reaction system have been studied in detail for the selective hydrogenation of BN to the primary amine of benzylamine (BA) with a Pd/Al 2 O 3 catalyst. The hydrogenation runs were conducted under different conditions and molecular interactions among the substrate, CO 2 , water, and the catalyst were measured by in situ high-pressure FTIR methods [16,17] in order to elucidate the roles of CO 2 and water. The medium of gas (H 2 , CO 2 ) -liquid (water) -liquid (BN) -solid (catalyst) has been confirmed to be effective for the selective production of BA by BN hydrogenation with no catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Using in situ high pressure FTIR techniques, a few authors investigated this phenomenon important in catalytic hydrogenation and other reactions in the presence of dense phase CO 2 . [9][10][11][12][13][14][15] Baiker et al used attenuated total reflection infrared spectroscopy (ATR-IR) to follow the reaction of CO 2 with H 2 over alumina-supported Pt catalyst in the form of thin film in cyclohexane at 313 K. 9,10,12 It is indicated that carbonate-like species are formed from CO 2 adsorbed on the support and then react with H 2 , forming CO. The formation of CO was responsible for the catalyst deactivation observed in hydrogenation of ethyl pyruvate in supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%